돈사 내에서 계절별 악취 발생 농도 조사 연구 - 감동환; 정종원; 최희철; 송준익; 홍준택; 이대원; 유용희; Kam, D.H; Jeong, J.W; Choi, H.C; Song, J.I; Hong, J.T; et al. (축산시설환경학회지, 2007)
Six pig farms were surveyed to measure the odor concentrations and characteristics of ammonia and sulfide corollary compounds in piggery. They were depended on the scale of piggery, weather conditions such as temperature, humidity, wind speed and direction, scales and types of pig breeding, and manure treatment methods. The highest ammonia concentrations in piggery were measured during the winter, since the tight sealed insulation in piggery made less amount of generated ammonia discharged from piggery. The objective of this study was to measure concentrations of odor in the piggery by season and growing, and to measure concentrations of odor at boundary area. So, we investigated the raising managements, manure managements, and methods of reducing odor according to farm scale. We found that concentration of ammonia gas in the swine fattening piggery in winter was the highest. This result is consistent with the lower ventilation rate to maintain Indoor temperature. In this result, there was no connection between farm scale and ventilating system. Concentration of ammonia gas was 1.64 ppm at one boundary area in the middle scale. $H_2S$, $CH_3SH$, $(CH_3)_2S$, and $(CH_3)_2S_2$ were below the standard of protection odor policy. 본 연구에서는 축산농가의 사육규모에 따른 사육형태, 분뇨처리 방법, 악취저감 방법 등과 계절별 성장단계별 돈사 내 악취농도와 환기방식이 다른 두 농장의 부지경계 지점의 악취농도를 조사 연구하고자 하였다. 1. 돈사 내 암모니아 발생량을 조사한 결과 겨울철 육성비육돈사의 암모니아 농도가 가장 높았다. 그 이유는 돈사 보온을 위해 적정 환기 유지보다 밀폐 강화 등의 결과로 돈사 내 발생한 암모니아 배출이 적어 농도가 높아지는 것으로 보였다. 2. 돈사 내 악취농도 조사 결과 사육규모와 환기 방식이 관계가 없는 것으로 나타났다. 3. 환기방식이 다른 농장 두 곳의 부지경계 지점을 조사하고 악취농도를 측정한 결과 부지경계 인근까지 돈사시설이 활용되고 있었다. 암모니아($NH_3$)는 한곳의 농장에서 1.64 ppm으로 조금 높게 검출되었으며 $H_{2}S$, $CH_{3}SH$, $(CH_3)_2S$, $(CH_3)_2S_2$는 악취방지 법의 배출 허용기준 이하로 검출되었다.